Proposed medications for taxane-induced myalgia and arthralgia (Review) - IMAI, ATSUSHI (D.A. Spandidos, 2012)
Taxanes inhibit the disassembly of microtubules, which are involved in mitosis and axoplasmatic transport, and may cause the degeneration of peripheral, mainly small, sensory nerves. Peripheral neurotoxicity is a dose-limiting side-effect of taxanes. Neuroprotective agents may aid in the reduction of neurotoxicity, thus allowing the intensification of cytostatic therapy in patients. An increasing number of medications for the prevention of taxane-induced arthralgia and myalgia are becoming available to oncology teams. The most widely studied medications include so-called analgesics such as Shakuyaku-kanzo-to (a herbal medicine), corticosteroids and antihistamines. Arthralgias and myalgias (muscle spasms, fasciculations and prolonged contractions) may be extremely distressing for patients. New anti-epileptic drugs, particularly gabapentin and pregabalin, have proven to be safe and effective in the treatment of taxane-induced neurotoxicity. The aim of this review was to examine the topical choices available for the protective management of taxane-induced neurotoxicity monitored in preliminary case studies and clinical trials. At present, there is no standard of care for the prevention of taxane-induced arthralgia and myalgia. In combination with taxane-based chemotherapeutic regimens, these medical agents may be crucial in the treatment of a variety of types of cancer.